Evidências para o cuidado perioperatório à mulher mastectomizada : revisão integrativa da literatura - Mourão, Carla Monique Lopes (2011)
It is an integrative literature review, which aimed to search and evaluate the available evidence in the literature on perioperative care provided to patients undergoing mastectomy. To select the studies were consulted the databases PUBMED, LILACS and CINAHL and the sample consisted of seven studies. No study has been identified in the databases LILACS and CINAHL, and all seven studies were from the PUBMED. There was a prevalence of 6 studies (86%) with level of evidence 2 and 1 study (14%) with level of evidence 3. After analyzing the issues addressed in these articles, gathered in atopical category: pain management, containing the seven studies. The first study found that a dose of 600 mg of gabapentin administered 1 h before surgery produces significant postoperative analgesia after total mastectomy. The second study showed that use of EMLA in mastectomy patientsreduced the request of analgesics postoperatively and a reductionin the incidence and intensity of chronic pain. In the study 03 found no differences in the management of postoperative pain between 3.75 mg / ml and ropivacaine wound infiltration with saline prior to mastectomy. The fourth study found that preventive administration of ketoprofen intravenously (100 mg) produces greater relief of postoperative pain in patients undergoing mastectomy. The fifth study showed that administration of dexamethasone 8 mgeffectively decreases the use of analgesics in women undergoinggeneral anesthesia for mastectomy. The sixth study showed no association between the index of nitric oxide and the development of chronic postoperative pain. The seventh study found that perioperative administration of venlafaxine significantly reduces the incidence of pain syndromeafter mastectomy. The study had limitations the fact that over the 10 years studied, the only perioperative care of the mastectomy surgery in the literature was related to the pharmacological management of pain and the studies analyzed did not show an association between them, since in each was assessed a different drug, hindering consensus and recommendation regarding the use of drugs to control / minimize the pain. The evidence did not show a consensus for the perioperative care of mastectomy, because we found a diversity of use of drugs for pain control and in most studies there were differences and division of opinion. However, we noted the concern on the part of professionals to minimize / prevent pain before, during and after surgery, and nursing must be attentive to both the update of pharmacological treatments in pain management, for the development of future research related to the care of perioperative nursing.